2004
DOI: 10.1530/rep.1.00211
|View full text |Cite
|
Sign up to set email alerts
|

Embryonic exposure to oestrogen causes eggshell thinning and altered shell gland carbonic anhydrase expression in the domestic hen

Abstract: Eggshell thinning among wild birds has been an environmental concern for almost half a century. Although the mechanisms for contaminant-induced eggshell thinning are not fully understood, it is generally conceived to originate from exposure of the laying adult female. Here we show that eggshell thinning in the domestic hen is induced by embryonic exposure to the synthetic oestrogen ethynyloestradiol. Previously we reported that exposure of quail embryos to ethynyloestradiol caused histological changes and disr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
32
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 29 publications
9
32
0
Order By: Relevance
“…In the duck, prostaglandin synthesis by the eggshell gland mucosa is observed after treatment with the weakly estrogenic p,p'-DDE, but not the more estrogenic o,p'-DDT or p,p'-DDT (43), suggesting that ESRs are not involved in this mechanism. However, studies in the chicken have demonstrated a likely ESR-dependent mechanism where in ovo exposure to EE 2 or the estrogenic o,p'-DDT results in production of thin shelled eggs as adults (44,45). Unlike the mechanism in adult birds, developmental exposure results in altered carbonic anhydrase expression and morphological alterations to the oviduct that likely persist throughout life (44,45).…”
Section: Discussionmentioning
confidence: 99%
“…In the duck, prostaglandin synthesis by the eggshell gland mucosa is observed after treatment with the weakly estrogenic p,p'-DDE, but not the more estrogenic o,p'-DDT or p,p'-DDT (43), suggesting that ESRs are not involved in this mechanism. However, studies in the chicken have demonstrated a likely ESR-dependent mechanism where in ovo exposure to EE 2 or the estrogenic o,p'-DDT results in production of thin shelled eggs as adults (44,45). Unlike the mechanism in adult birds, developmental exposure results in altered carbonic anhydrase expression and morphological alterations to the oviduct that likely persist throughout life (44,45).…”
Section: Discussionmentioning
confidence: 99%
“…Programming is defined as the physiological 'setting' by an early stimulus or insult during a 'sensitive' period, resulting in long-term consequences for function (Lucas et al, 1991). Exposure to exogenous estrogen or progestin during early life stages has been shown to cause reproductive toxicity in mammals, reptiles, birds, fish, and amphibians (Atanassova et al, 2000;Berg et al, 2004;Blomqvist et al, 2006;Crain et al, 2008;Goyal et al, 2003;Gray et al, 2001;Gyllenhammar et al, 2009;Hill and Janz, 2003;Kvarnryd et al, 2011;Maunder et al, 2007;Pettersson et al, 2006). This research shows that developmental estrogen exposure targets the differentiation of the testis and Müllerian ducts (embryonic precursor of female reproductive tract) in amphibians, birds and mammals (Atanassova et al, 2000;Berg et al, 2004;Blomqvist et al, 2006;Crain et al, 2008;Goyal et al, 2003;Gyllenhammar et al, 2009;Hill and Janz, 2003;Maunder et al, 2007;Pettersson et al, 2006), and that developmental progestin exposure targets Müllerian duct differentiation and oocyte development in amphibians and mammals (Chen et al, 2007;Gray et al, 2001;Kezele and Skinner, 2003;Kvarnryd et al, 2011;Nilsson and Skinner, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…However, few isozymes of other origin have been investigated in detail. This is particularly true for birds (Aves), for which different reports mention the role of CAs in the eggshell formation for chicken (Gallus gallus) and ostrich (S. camelus), but few attempts have been undertaken to isolate, characterize, and investigate the inhibition of these enzymes were done [15][16][17][18][19][20] . Here, we report on the purification of a CA from pigeon red blood cells as well as on the first inhibition study of this enzyme with a series of aromatic and heterocylic sulfonamides.…”
Section: Resultsmentioning
confidence: 99%
“…Among birds, the red blood cell enzyme from the ratid Struthio camelus (ostrich) 15 has been investigated in some detail, but as outlined above, these data for enzymes which are of non-human or non-rodent origin, are rather scarce. In the case of birds (Aves), there are several reports on CAs from chicken (Gallus gallus) and ostrich (S. camelus) [16][17][18][19][20] but no attempts were made to isolate, characterize, and study the inhibition of these enzymes were done, except for the ostrich enzyme which has been investigated in detail in this study 15 . It is interesting to note that Thomas 17 reported previously in a preliminary work about some CA activity of pigeon erythrocyte.…”
Section: Introductionmentioning
confidence: 99%